Gender, spousal caregiving, and depressive symptoms among Chinese older adults: does work status matter?. (2nd January 2023) - Duan, Haoshu; Chen, Feinian
Abstract: Objectives: This study aims to examine the impacts of spousal caregiving on caregivers' depressive symptoms, and how work status and gender mitigate the relationship. Method: We used four waves' data from the China Health and Retirement Longitudinal Study (CHARLS, 2011-2018, N  = 20, 213) with linear mixed-effect models to investigate the association between providing instrumental activities of daily living (IADL) and activities of daily living (ADL) assistance to a spouse and spouse caregivers' depressive symptoms. We further examined the moderating effect of work status. Analyses were stratified by gender. Results: As main effects, respondents who provided ADL assistance to their spouse had significantly higher depressive symptoms than non-spousal caregivers, and the association was particularly stronger for women than for men. However, we did not find significant difference of depressive symptoms between IADL spousal caregiver and non-spousal caregivers. Working while ADL spousal care further exacerbated caregivers' depressive symptoms for both genders, whereas working full-time while providing IADL spousal care is only associated with elevated depressive symptoms for women. Interestingly, we found that providing IADL assistance is associated with lower depressive symptoms while they were not working. Conclusion: The relationship between spousal caregiving and depressive symptoms differed significantly by the type of care and was also moderated by work status, and female caregivers on average have worsened depressive symptoms than male caregivers. Future research on caregiving needs to consider the types of care and other social roles that caregivers also take on. Lastly, more affordable eldercare facilitates need to be built to alleviate the burden among spousal caregivers, especially when they are working.